Modelling of phase equilibrium in chloroform – ethanol – ionic liguid system - S. L. Nazanskiy; V. I. Zhuchkov; A. K. Frolkova (Тонкие химические технологии, 2014)
The mathematical model for system, containing ethanol, chloroform and 1-ethyl-3-methylimidazoliumtrifluorosulphonate is obtained. NRTL binary parametres are evaluated and vapor-liquid equilibrium is calculated. The possibility of separation ethanol-chloroform mixture with ionic liquid as extractive agent is evaluated.